(untitled) (Transport systems and technologies, 2021)
The publication proposes a monitoring technology for production automation based on automatic identification technologies, which will allow real-time monitoring of the progress of technological processes, ensure interdepartmental logistics, as well as perform access and identification security functions in production. On the example of one of the carriage depots, typical shortcomings of the organization of the production process, accounting and identification of parts of a railway transport enterprise are considered. The ways and stages of implementation of automatic identification technologies are proposed, in particular, it is indicated that it is advisable to introduce a system for monitoring production processes of railway transport enterprises in stages, starting with bar-coding technologies. The process of monitoring railway transport enterprises, the interaction of subjects and objects of the production process is disclosed in detail.